What lactation issues occur from using DMPA for contraception in the immediate postpartum period?. Issue 10 (October 2015) - Hermann, Sophia; Grogan, Scott
Abstract : Evidence‐Based Answer : Immediate depomedroxyprogesterone (DMPA) does not appear to decrease the rate of breastfeeding continuation or the amount of breastmilk produced (SOR: B, cohort trials). Immediate DMPA is recommended to prevent close interval pregnancy in at‐risk populations (SOR: C, expert opinion).